Foreign Policy of the Republic of Indonesia in the Palestine-Israel Conflict from a Normative Theory Perspective - Alya Medina; Wawan Budi Darmawan; Dina Yulianti (Ilomata International Journal of Social Science, 2026)
The Palestine–Israel conflict, is one of the most complex and prolonged issues in modern international politics, marked by an acute humanitarian crisis since the establishment of the State of Israel in 1948. In this context, Indonesia holds a distinctive position as a country that has consistently supported the Palestinian struggle, from the era of President Soekarno to President Joko Widodo. This research, aims to analyze Indonesia's foreign policy toward the Palestine–Israel issue through the lens of normative theory in International Relations, which emphasizes the importance of moral values, ethical principles, and international norms in state decision-making. Utilizing a qualitative method based on literature studies and in-depth interviews, this study explores how the constitutional foundation of the 1945 Constitution, the values of Pancasila, and the nation's moral identity shape Indonesia’s consistent stance in international forums. The findings reveal, that Indonesia’s support for Palestine is not merely a political strategy or a response to global dynamics, but rather a representation of a normative commitment to justice, human rights, and anti-colonial principles. The normative theory approach in this study demonstrates that Indonesia’s foreign policy reflects the nation’s ethical identity as well as its moral stance in confronting global injustices experienced by the Palestinian people. This research contributes to a deeper understanding of how normative theory can be applied to analyze foreign policy in the Global South, particularly in post-colonial contexts. The study also provides insights for policy makers and scholars in recognizing the enduring role of ethical considerations in shaping international relations.